The divergent dynamics of economic growth : studies in adaptive economizing, technological change, and economic development - Day, Richard Hollis (Cambridge, UK ; New York, NY : Cambridge University Press, 2004)
This book introduces 40 years of original work on the dynamics of economic growth by an exceptionally creative economist. Professor Day uses recursive models to synthesize classical, neoclassical, and evolutionary points of view and empirically tests his approach on economic sectors where change is rapid and also on epochal changes in social systems.
Includes bibliographical references and index.
gau 18/06/14, ijb 05/02/2019
Loans
Keywords: Technological innovations - Economic aspects; Economic development; Evolutionary economics